Pengaruh Modal Sosial Terhadap Praktik Manajemen Rantai Pasok Hijau dan Kinerja Rantai Pasokan - Muhammad Rayzan Muvasha; Wahyuningsih Santosa; Ratna Darasih; Dorina Widowati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study examines the effect of structural and relational social capital on Green Supply Chain Management Practices (GSCMP) and their impact on Supply Chain Performance (SCP) in Indonesia’s shipyard industry. Using a quantitative, cross-sectional approach, data were collected from shipyard employees in Samarinda and Surabaya through a 140-item questionnaire and analyzed using Structural Equation Modeling (SEM). The findings indicate that both forms of social capital significantly and positively influence GSCMP and supply chain performance. GSCMP improves operational efficiency and supports organizational sustainability; however, further improvements are needed in Total Quality Environmental Management (TQEM) and scrap material management to better meet customer requirements.